ANALISIS FATWA-FATWA SEMASA SYARIAH DI MALAYSIA - Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
In Malaysia, a fatwa means a decision officially given by a Mufti or a Shariah State Committee published in the State Official Gazzate. Once a fatwa is published in this fashion it becomes binding upon all Muslims residing in the state. The present article investigates some issues relating to the administration of fatwa in Malaysia especially in regards to the trends and problems these fatwas attempt to solve.